BIMBINGAN INDIVIDU BAGI SANTRI HOMESICK (Penelitian Pada Kelas VII Pondok Pesantren Modern Asy Syifa, Desa Tambakmekar, Kecamatan Jalan Cagak, Kabupaten Subang) - Sabila, Elsa; Muksin, Ucin; Miharja, Sugandi (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The purposes of this study are: To find out individual guidance to deal with students who experience homesick in Asy Syifa modern Islamic boarding schools, To determine the condition of students who experience homesick in Asy Syifa modern Islamic boarding schools, To find out the results of individual guidance to students who experience homesick in Islamic boarding schools modern Asy Syifa. The research method used by the researcher is descriptive research method. Furthermore, in scientific writing, the researcher uses a qualitative research type, where the basis of this research is the phenomena and reality that develop in the life of the research object according to the results in the field regarding individual guidance for homesick students at the modern Islamic boarding school Asy Syifa Subang. The results of the implementation of individual guidance on homesick students of class VII Pondok Pesantren Modern Asy Syifa showed a good change.